Mitigating salinity stress on tomato growth, water regime, gas exchange, and yield with the application of QuitoMax - Leandris Argentel-Martínez; Ofelda Peñuelas-Rubio; Carlos Ávila Amador; Fábio Steiner; Jorge González Aguilera; Jae-Ho Shin; Alan Mario Zuffo; Rafael Felippe Ratke; Paulo Eduardo Teodoro; Ugur Azizoglu (Scientific Reports)
Abstract This study assessed the intensity of salt stress in the two tomato varieties by measuring variables associated with the water regime, chlorophyll content, normalized difference vegetation index, gas exchange, and yield. The cultivars Amalia and Claudia, which represent tolerance and susceptibility to salinity, were evaluated. Three treatments were established in plastic pots, using a completely randomized design: T1, saline soil (ECse = 6.9 dS m−1 without QuitoMax application); T2, nonsaline soil (ECse = 0.95 dS m −1 with QuitoMax application); and T3, saline soil (ECse = 6.9 dS m−1) with QuitoMax application. The QuitoMax was applied at a rate of 300 mg L-1, during the flowering phenophase. QuitoMax caused an increase in the variables evaluated in both varieties (tolerant and susceptible) of tomato, with a lower contribution of QuitoMax to the variables related to water regime and the greatest contributions to chlorophyll content and photosynthetic activity. QuitoMax contributed positively to all variables and was superior to stress intensity for most of the variables evaluated in the tolerant variety (Amalia), except for stem thickness and the number of flowers per bunch. In the susceptible variety (Claudia), the five variables of stress intensity exceeded the contribution of QuitoMax, with the strongest effects on osmotic potential, fruit mass, and yield per plant. The present work demonstrates the feasibility of using this biostimulant to increase the tolerance of tolerant varieties and maintain tolerance in tomato varieties susceptible to salinity, reducing the intensity of saline stress and increasing plant performance under salinity conditions.